Case Report: Advanced breast invasive ductal carcinoma with erysipeloid cutaneous metastasis misdiagnosed as erysipelas - Gu, Weiju; Yuan, Jing; Dong, Mengting; Sheng, Jiayu; Jiang, Ke (Frontiers in Oncology, 2025)
BackgroundBreast cancer has become the second most common cancer after lung cancer. Patients may present with skin manifestations at the time of initial diagnosis, while erysipel-like carcinoma typically appears later, following initial treatment. This delay increases the risk of misdiagnosis.Case presentationThe patient was a 51-year-old female. A modified radical mastectomy for left breast carcinoma (pT2N3M0, stage IIIC; tumor size 4.6 cm × 4.5 cm × 1.6 cm, 14/21 axillary lymph nodes involved), HER2-positive type, was performed on April 21, 2021. In April 2024 (three years post-surgery), the patient developed unexplained redness and swelling in the skin of the left upper limb, accompanied by increased skin temperature. This was misdiagnosed as erysipelas of the upper limb. After one week of antibiotic treatment, the redness and swelling slightly subsided. In May 2024, the patient experienced dizziness and headaches without any obvious cause. Enhanced cranial MRI revealed multiple brain metastases, with possible lymph node metastasis in the left cervical region. The patient underwent whole-brain radiotherapy. During radiotherapy, erysipelas-like rashes developed on the left chest wall, upper limb, and right breast skin. In June 2024, a skin biopsy of the chest wall confirmed cutaneous metastasis. Following systemic anti-tumor treatment, both the skin and brain metastasis improved.ConclusionPathological biopsy should be emphasized when breast cancer patients develop localized rashes. Understanding the unique inflammatory manifestations of cutaneous metastasis is crucial for breast oncologists to enable early diagnosis, timely treatment, and improved overall survival.